Analisis Faktor Determinan Financial Distress (Studi Empiris Pada Perusahaan Go Public di Indonesia) - Alya Quinia Yasmine; Liza Alvia (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
This study aims to determine the effect of return on assets (ROA) and CSR disclosure on financial distress in trading sector companies registered on the Indonesian Stock Exchange during 2020-2021. The research method uses quantitative methods. The population in this study are trading sector companies listed on the Indonesian Stock Exchange. Based on the sample selection criteria, a sample of 82 companies was obtained. The data analysis technique used is descriptive statistical analysis, testing the entire model, coefficient of determination, model feasibility test, simultaneous model significance test, and partial model significance test. The results of the study show that ROA have an effect on financial distress. Meanwhile, CSR disclosures proxied by managerial ownership and the proportion of independent commissioners have no effect on financial distress. The coefficient of determination of 58,6 percent indicates the ability of ROA and CSR disclosure to explain changes in financial distress of 58,6 percent, while the remaining 41,4 percent is explained by other factors.